The Relationship Between Corporate Social Responsibility and Earnings Management: An Exploratory Study - Hong, Yongtao; Andersen, Margaret L. (2011)
In this article, we explore the relationship between corporate social responsibility (CSR) and earnings management (EM). Our CSR index, using KLD data, incorporates information from the following issue areas: the community, corporate governance, diversity, the product, employee relations, the environment, and human rights. Results show that more socially responsible firms have higher quality accruals and less activity-based EM, both of which impact financial reporting quality.
Keywords: KLD database; Ethics; Earnings management; Corporate Social Responsibility; Accruals quality